A Thematic Approach to Teach Introductory Sociology - Albert E. McCormick Jr. (Journal of Public and Professional Sociology)
Soon into his career, the author discerned several pedagogic flaws in introductory sociology texts. Responding to these flaws, he organized his introductory course around the theme of social change. This theme serves as a background for and lead-in to just five other topic areas amenable to a basic understanding of the discipline: demography, social differentiation, social stratification, the family, and deviance. Sociological theory, statistics, and methods are linked to these substantive topic areas only where appropriate. Topics are covered in depth and important concepts are directly illustrated by college-level readings, written by sociologists. The result was the development of an integrated and cohesively presented course in which the instructor had total control of the pace, content, depth of coverage, and level of presentation. For an introductory class that is both effective and satisfying to teach, the author suggests that other instructors base their courses on their own areas of interest and expertise. Such a course should be accompanied by a set of college-level sociological readings selected to illustrate the topic areas and concepts the instructor has chosen to present.